GERAKAN DAKWAH CINTA TANAH AIR INDONESIA (Strategi dan Metode Dakwah KH. Habib Luthfi Pekalongan) - Syaefuddin, Machfud (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2017)
Movement of da'wah love the homeland Indonesdia by KH. Habib M. Luthfi quite relevant in the midst of the condition of the Indonesian nation today. As scholars, kiai, and Sufi religious leaders (Rais amm jam'îyah expert ath-tharîqah al-mu'tabarah an-nahdhîyah) have played an important role to foster nationalism and consistently dak’wah Islam in particular in an effort to affirm the spirit of love of the homeland and nation. Shia Islam and love of the country have gained an emphasis on every event of dakwah. So what is done looks thick with the attribute of love homeland. Affirmation of the love of the homeland is very important to be done by all parties, including for missionaries as the bearer of Islamic mission rahmatan lil alamin. Specialness da'wah KH. Habib M. Luthfi seems to be a massive missionary movement in an effort to care for and maintain the integrity of the unitary republic of Indonesia. The da'wah movement among others: always frame the maze of kanzus sholawat in the nuances of nationalism, organize conferences and scientific forums love the homeland, promoting and singing poems songs insightful nationalism, composing a series of nationalism nuances, designing and installing banners and famlet thick with nuances keindonesiaan, as well as establishing friendship with various groups of children of the nation.